Use of Hen Egg Derived Immunoglobulin Against Scolopendra (Scolopendra Gigantea) Venom - Parrilla-Alvarez, Pedro; Navarrete, Luis F.; Aguilar, Irma; Rodríguez-Acosta, Alexis (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
A scolopendra sting in humans and domestic animals is an acute and highly painful accident. The present study was an attempt to raise specific hyper-immune polyclonal antibodies against scolopendra centipede (Scolopendra gigantea Linneaus 1758) venom. A group of hens were injected with venoms subcutaneously and intramuscularly according to three different routines. This protocol was found to be effective for hyperimmunization. Eggs were gathered daily and antibodies were purified from yolk with a polyethylene-glycol and chloroform modified method. Titers of antibodies in yolk were estimated with an agar gel precipitation test, and a serum protection (ED50) test. Eggs harvested at 15 days post-injection had maximum antibody titers. After six months, antibodies lyophilized and stored at 5°C still maintained their activity. Envenomed mice were injected with purified antibodies, which induced 100% recovery as compared to those not treated with the antibodies. The cleanliness, effectiveness, and simplicity of producing antibodies against scolopendra venom in avian egg yolk, and their incapability to attach human complement, formulates an interesting option to equine and other mammalian antivenoms. This study infers that avian egg yolk antibodies may be useful as a therapeutic tool in treating scolopendrism in humans and domestic animals. It also opens a field for the production of other antivenoms against the wide spectrum of toxins as well as the use of these antibodies as a diagnostic tool